2015
DOI: 10.1891/1540-4153.13.4.179
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of a Virtual Patient Educator for Hispanic Women

Abstract: There are few Spanish language interactive, technology-driven health education programs. Objectives of this feasibility study were to: 1) learn more about computer and technology usage among Hispanic women living in a rural community; and 2) evaluate acceptability of the concept of using an embodied conversational agent (ECA) computer application among this population. A survey about computer usage history and interest in computers was administered to a convenience sample of 26 women. A sample video prototype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…For example, mobile phone penetration among farmworkers has been found to be comparable to the general Latino population [120]. Furthermore, in cases where there is a lack of technology access, there are examples in the literature where technology was incorporated at the community level [28]. To avoid widening intragroup health disparities, future research should ensure that the needs of these subpopulations are met.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, mobile phone penetration among farmworkers has been found to be comparable to the general Latino population [120]. Furthermore, in cases where there is a lack of technology access, there are examples in the literature where technology was incorporated at the community level [28]. To avoid widening intragroup health disparities, future research should ensure that the needs of these subpopulations are met.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research has explored the feasibility, acceptability, and efficacy of these tools in promoting health [15,22-26]. While challenges remain in the standardized evaluation and cost-benefit analysis of consumer health IT [27,28], initial studies have shown potential for these engagement-oriented tools to positively impact health outcomes, quality of life, hospital readmission rates, and mortality [29-34]. …”
Section: Introductionmentioning
confidence: 99%
“…For those whose primary language is not English, accessing information or using these technologies can be a very difficult and complex task (Wells, Vazquez-Otero, Bredice, Meade, & Chaet, 2015). Concerns with limited knowledge regarding use of computers and similar technologies, as well as level of education and use of technology, may affect the utilization of internet programs among Hispanic women (Wells et al, 2015). Among Hispanics who have not completed high school, internet use is estimated to be at 31% (Fox & Livingston, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Before design and development, an initial feasibility study was conducted in order to assess the previous exposure of our female Hispanic farmworkers to computers and technology and the preliminary acceptability of a virtual agent application among this population [25]. Contradictory to our expectations that female Hispanic farmworkers have limited access to computers, after interviewing 26 Hispanic women who received health care at CMMS, 61.5% of them reported to have used a computer before.…”
Section: Initial Feasibility Studymentioning
confidence: 99%